Analysis of Consumer Acceptance of Three Milk Brands Using Hedonic Testing in Jember Regency - Helda Jaya Puspita; Rini Hardiyani; Rallyanta Tarigan; Amalia Malik; Canggih Nailil Maghfiroh (Green Engineering Society, 2026)
Milk is a highly nutritious food that plays an important role in meeting the nutritional needs of the community, making consumer acceptance a key factor in the success of dairy products in the market. Various brands of factory-produced liquid milk have long been available in the Indonesian market and possess different product characteristics and market positions. Therefore, a comparison of consumer acceptance based on sensory attributes is necessary to better understand consumer preferences for each brand. This study aims to analyze consumer acceptance of three brands of factory-produced liquid milk marketed in Jember Regency's modern markets based on sensory attributes. The research used a hedonic test method involving 78 untrained panelists from the general public. The samples tested consisted of three milk brands (Greenfields, Ultra Milk, and Diamond) with three flavor variants: full cream, strawberry, and chocolate. The sensory attributes observed included color, aroma, taste, and viscosity, using a five-point hedonic scale. Data were analyzed using analysis of variance (ANOVA) at a significance level of 5% and followed by Duncan's test if significant differences were found. The research findings indicate that brand variations significantly impact the aroma, taste, and viscosity characteristics in the majority of variants, whereas the effect on color is contingent upon the specific flavor variant. The Diamond sample demonstrated the highest acceptance level in the full-cream milk variant, likely due to its higher total fat content. In the strawberry milk variant, all sensory attributes were significantly influenced by brand differences, with the Greenfields sample having the highest preference level, supported by its more attractive color and balanced flavor due to its higher sugar and fat content. In the chocolate milk variant, brand differences significantly affected the color, aroma, and taste attributes, while viscosity showed no difference. Overall, sensory attributes, particularly taste and aroma, are important factors that influence consumer acceptance of dairy products.